Smoking and caesarean deliveries: major negative predictors for breastfeeding in the mother–child cohort in Crete, Greece (Rhea study) - Vassilaki, Maria (Matern Child Nutr, 2012)
Although benefits of breastfeeding have been widely promoted and accepted, exclusive breastfeeding for the first 6 months of life is far from the norm in many countries. In a prospective mother–child cohort study in Crete, Greece (‘Rhea’ study), we assessed the frequency of breastfeeding and its socio‐demographic predictors. Information on breastfeeding was available for a period of 18 months post‐partum for a cohort of 1181 mothers and their 1208 infants. The frequency of exclusive and predominant breastfeeding in the first month post‐partum was 17.8% and 3.4%, respectively, with almost three‐quarters of women (73.6%) ceasing any breastfeeding after 4 months post‐partum. Women were less likely to initiate breastfeeding if they had a caesarean delivery (CD), whereas they were more likely to initiate breastfeeding if they had a higher education or gave birth to a private clinic. Among women breastfeeding, those who had a CD, were ex‐smokers or smokers during pregnancy had a statistically significant shorter duration of breastfeeding, whereas higher education and being on leave from work were associated with a longer duration of breastfeeding. Study findings suggest suboptimal levels of exclusive and any breastfeeding and difficulty maintaining longer breastfeeding duration. CD and smoking are common in Greece and are strong negative predictors for breastfeeding initiation and/or duration, necessitating targeting women at risk early in the prenatal period so as to have a meaningful increase of breastfeeding practices in future cohorts of mothers.